DATA TO BUILD A BASELINE OF INFORMATION TO STRENGTHEN THE GENERATION OF RURAL COMMUNITY TOURISM IN SAN JUANITO MUNICIPALITY OF META COLOMBIA - , (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
An information baseline was structured to analyze the tourist potential of the area of ??influence of the Chingaza National Natural Park; this to determine the strengths to develop an approach to rural tourism as a sustainable alternative management of the territory in SanJuanito municipality of Meta, Colombia. A descriptive type mixed methodology was used, collecting secondary order information crossing it with the primary order data provided by the interested community obtained in the field. The relevance information of tourism in the National Natural Parks and the proposal of tourist areas made by the community of the San Juanito municipality were contrasted; 11 points as tourist attraction were proposed by the community, where only one is in the area of the ChingazaNational Natural Park, constituting a rural community tourism as a fortress for sustainable recovery points of interest, as well as related areas.